2004
DOI: 10.1124/mol.104.003624
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Negative Binding Cooperativity within CCR5-CCR2b Heterodimers

Abstract: It is well established that most G protein-coupled receptors are able to form homo-and heterodimers, although the functional consequences of this process often remain unclear. CCR5 is a chemokine receptor that plays an important role in inflammatory diseases and acts as a major coreceptor for human immunodeficiency viruses. CCR5 was previously shown to homodimerize and heterodimerize with CCR2b, a closely related receptor. In the present study, we have analyzed the functional consequences of this dimerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
128
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 31 publications
10
128
1
Order By: Relevance
“…The coupling of the receptors to different transducing pathways, PLC/IP 3 under basal conditions and adenylyl cyclase/PKA under depolarizing conditions, may have a number of explanations. For instance, it was shown that the chemokine receptors exist as homodimers or heterodimers and that the dimer composition can direct the coupling to different transducing pathways (Mellado et al, 2001;El-Asmar et al, 2005;Springael et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The coupling of the receptors to different transducing pathways, PLC/IP 3 under basal conditions and adenylyl cyclase/PKA under depolarizing conditions, may have a number of explanations. For instance, it was shown that the chemokine receptors exist as homodimers or heterodimers and that the dimer composition can direct the coupling to different transducing pathways (Mellado et al, 2001;El-Asmar et al, 2005;Springael et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the group of Parmentier elegantly demonstrated that binding of the CCR2 radioligand 125 I-monocyte chemoattractant protein-1 could be partially inhibited by the selective CCR5 agonist macrophage inflammatory protein-1␤, the maximal inhibition being correlated with the expected amount of CCR2-CCR5 heterodimers in the cell (El-Asmar et al, 2005). Conversely, binding of the CCR5 radioligand could also be partially inhibited by a CCR2 specific agonist, further demonstrating a negative cooperativity between the two binding sites in a CCR2-CCR5 heterodimer.…”
Section: E the Ccr2 And Ccr5 Receptorsmentioning
confidence: 99%
“…Although they may function as monomers, it is now well established that many chemokine receptors also act as dimers or higher order oligomers. 172 In fact, all tested chemokine receptors form oligomers in a ligand-independent manner, [173][174][175][176][177] and heterodimers can form even between CC and CXC subclasses. 172 Another relevant phenomenon is that of crosstalk between different receptors.…”
Section: Chemokines As Therapeutic Targetsmentioning
confidence: 99%